Soldiers - Haugen, David M., 1969- (San Diego : Blackbirch Press, 2004)
A history of the Revolutionary War, as told through diary excerpts, letters, and personal narratives from soldiers, military leaders, medical personnel, and other combat eyewitnesses.
Includes bibliographical references (p. 31) and index.
Keywords: United States. -- Continental Army -- Biography -- Juvenile literature; Great Britain. -- Army -- Biography -- Juvenile literature; Soldiers -- United States -- Biography -- Juvenile literature; Soldiers -- Great Britain -- Biography -- Juvenile literature; Soldiers; United States -- History -- Revolution, 1775-1783 -- Personal narratives -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Personal narratives